2002
DOI: 10.1523/jneurosci.22-24-11035.2002
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Analysis of Ethanol-Induced Locomotor Stimulation inDrosophila

Abstract: Understanding how ethanol influences behavior is key to deciphering the mechanisms of ethanol action and alcoholism. In mammals, low doses of ethanol stimulate locomotion, whereas high doses depress it. The acute stimulant effect of ethanol has been proposed to be a manifestation of its rewarding effects. In Drosophila, ethanol exposure transiently potentiates locomotor activity in a biphasic dose- and time-dependent manner. An initial short-lived peak of activity corresponds to an olfactory response to ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
260
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(274 citation statements)
references
References 36 publications
4
260
0
Order By: Relevance
“…The first assay is based on previous studies that measured rapid odor-induced startle responses (19,20). In this odor flow assay, individual flies are placed in circular arenas [ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first assay is based on previous studies that measured rapid odor-induced startle responses (19,20). In this odor flow assay, individual flies are placed in circular arenas [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously described fly olfactory assays retain little temporal or spatial information about odor-induced behavior (13-18). Therefore, we designed two olfactory assays that measure responses of individual flies to an odor stimulus at high spatial and temporal resolution.The first assay is based on previous studies that measured rapid odor-induced startle responses (19,20). In this odor flow assay, individual flies are placed in circular arenas [ Fig.…”
mentioning
confidence: 99%
“…Using invertebrate model systems for the study of ethanol's effects on the nervous system conveys several advantages, especially because many cellular mechanisms appear to be conserved across animal phyla (Wolf and Heberlein, 2003). In particular, studies using locomotor assays have extended what is known with respect to the molecular targets of ethanol in the central nervous system (Davies, et al, 2003;Moore, et al, 1998;Morgan and Sedensky, 1995;Wolf, et al, 2002). Using the fruit fly, Drosophila melanogaster, and the nematode, Caenorhabditis elegans, these studies have elegantly shown that ethanol interacts with calcium-activated potassium channels (Davies, et al, 2003), GABA B receptors (Dzitoyeva, et al ., 2003), and signaling via dopamine (Bainton, et al, 2000) and cAMP (Moore, et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recently several techniques have been developed to track social behaviors in animals with rigid exoskeletons, such as the fruit fly Drosophila, which have relatively few degrees of freedom in their movements (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These techniques have had a transformative impact on the study of social behaviors in that species (2).…”
mentioning
confidence: 99%